Voter Turnout Among First-Time Voters in the Gorontalo City Mayoral Election in Buladu Subdistrict, Gorontalo City - Wahfiyudin N. Laparako; Rauf A. Hatu; Dewinta Rizky R. Hatu; Vanya Dyah Pitaloka Maharani Ayuningtyas Catya Ramadhani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Awareness of the importance of participating in elections can begin with first-time voters aged 17 to 21. The purpose of this study is to determine the motivations behind the voting decisions of first-time voters in the Gorontalo City Mayoral Election in Buladu Village, Kota Barat District. This study employs a qualitative descriptive approach. The data collected were not numerical but were obtained from various sources, such as interview results, field notes, personal documents, and other official documents. The data collection techniques used included observation, interviews, and documentation. Meanwhile, the selection of informants was conducted according to the research needs. The data analysis process was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that first-time voters in Buladu Village are influenced by several factors in deciding which candidate to choose, including parental influence, employment, dawn raids or vote-buying practices, and their level of awareness regarding the local elections. This suggests that the rationality of first-time voters remains at the level of bounded rationality, consistent with James S. Coleman’s theory of rational choice, which posits that individuals make decisions based on a cost-benefit analysis. A synthesis of the main findings of this study indicates that the political decisions of first-time voters are influenced not only by personal rational considerations but also by social, economic, and environmental factors that shape their patterns of political participation. These conditions suggest that first-time voters are still in the process of developing independent and critical political awareness when making their choices in local elections. In conclusion, first-time voters in Buladu Village are still in a transitional phase, moving from passive and normative participation toward more active participation; however, their choices in the 2024 Gorontalo City Mayoral Election are not yet fully rational and independent, as they remain influenced by parental factors, the environment, the practice of vote-buying, and a lack of political education.